2018
DOI: 10.1007/s40273-018-0668-8
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Pharmacological Treatments for Asthma: A Systematic Review

Abstract: The present findings are in line with the pharmacological recommendations for stepwise management of asthma given in the most recent evidence-based clinical practice guidelines for the disease. The identified reporting quality of the available health economic evidence is useful for identifying aspects where there is room for improvement in future asthma cost-effectiveness studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 108 publications
1
16
0
1
Order By: Relevance
“…The current review faces similar difficulties in cross‐study comparison as Kim et al does, and it supports the need for standardized data sources and methods. Similar to the general findings of Rodriguez‐Martinez et al, the results of our review also found the quality of the reporting of the study methods to be variable, thus introducing the potential for some uncertainties in several important aspects relating to the methods and relevance of data used.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The current review faces similar difficulties in cross‐study comparison as Kim et al does, and it supports the need for standardized data sources and methods. Similar to the general findings of Rodriguez‐Martinez et al, the results of our review also found the quality of the reporting of the study methods to be variable, thus introducing the potential for some uncertainties in several important aspects relating to the methods and relevance of data used.…”
Section: Discussionsupporting
confidence: 83%
“…A few SRs conducted of EE studies for the treatment of childhood asthma were identified. Ungar (2009) only assess pediatric population, while further reviews assessed both adult and pediatric population EEs . The current review aimed to systematically review and critically appraise the literature of EEs that focuses specifically on pediatric asthma and takes a broader view of eligible treatments (both pharmaceutical and non‐pharmaceutical interventions).…”
Section: Introductionmentioning
confidence: 99%
“…Another review of 72 studies assessing the cost‐effectiveness of asthma treatment reported that among patients with uncontrolled severe persistent allergic asthma, omalizumab could be cost‐effective in patients with more severe disease. The quality among studies was uneven and the main cost‐effectiveness drivers were the cost or rate of asthma exacerbations, the cost or rate of use of asthma medication, asthma mortality risk and the rate of utilization of health services for asthma …”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews of the cost effectiveness of biologics for the treatment of asthma demonstrated that time horizon and drug price are among the key drivers of the incremental cost-effectiveness ratio 45,46 . Differences in drug prices between countries strongly impact cost effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Cost-effectiveness analyses of biologics focus on the defined subpopulations of patients with severe disease for whom these treatments are most clinically effective 45,46 . The incremental cost-effectiveness ratio from our analysis of benralizumab of SEK 366,855 (e34,127) is comparable to values reported for use of mepolizumab and reslizumab in the UK, although those values required substantial discounts in UK pricing [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%